Antioxidant Activity of Essential Oils from Pinaceae Species - Robert Ancuceanu; Adriana Iuliana Anghel; Marilena Viorica Hovaneț; Anne-Marie Ciobanu; Beatrice Elena Lascu; Mihaela Dinu (MDPI AG, 2024)
With a widespread distribution throughout the Northern Hemisphere and 11 genera, Pinaceae is the largest family of Gymnosperms in the world. Essential oils are an important chemotaxonomic marker for the species of this family, although the degree of chemical and biological investigation has not been the same for all genera. Essential oils from Abies and Cedrus (from the abietoid clade) or Pinus and Picea (from the pinoid clade) have been more extensively investigated with respect to their chemical composition and biological or pharmacological properties, including their antioxidant effects. Instead, essential oils from the other genera of the family have been less explored in this respect or even have not been investigated at all. This is a narrative review looking into the knowledge acquired up to date, the variability and limitations of the current methods used to estimate antioxidant effects, and multiple comparisons between EOs obtained from different genera, species, and plant parts, as well as potential applications and future directions of research and utilization of essential oils derived from Pinaceae species.